Molecular Docking Terpinen-4-ol pada Protein IKK sebagai Antiinflamasi pada Aterosklerosis secara In Silico - Dewi, Putu Pradnya Pramita (Jurnal Farmasi Udayana; Vol. 8, No. 1, Tahun 2019DO - 10.24843/JFU.2019.v08.i01.p07, 2019)
ABSTRACT   Atherosclerosis is a chronic inflammatory disease that begins with endothelial dysfunction, it caused fat accumulation and plaque growth in the inner arteries walls. Endothelial dysfunction will activate the Nuclear Factor Kappa B (NF-kB) pathway involving IKK proteins. Terpinen4-ol is constituent found in the bangle (Zingiber cassumunar) rhizome. The purpose of this study were to determine the affinity and mechanisms of terpinen-4-ol against IKK protein as anti-inflammatory in atherosclerosis performed using molecular docking method. The docking result are assessed from the binding energy and hydrogen bonds formed between terpinen-4-ol and protein. The result showed that terpinen-4-ol has activity in inhibiting the inflammatory process because it is able to disturb IKK protein with bond energy values -4.89 kcal/mol. The molecular mechanism in inhibiting the activity of IKK protein through the formation of hydrogen bonds in these proteins. These result show that terpinen-4-ol has the potential to inhibiting inflammatory process and it caused the formation of atherosclerotic plaque can be obstructed.   Keywords: Atherosclerosis, Terpinen-4-ol, Molecular Docking, In Silico